MEMS based Hand Gesture Wheel Chair Movement Control for Disable Persons (International Journal of Current Engineering and Technology, 2015)
This project is to develop a wheel chair control which is useful to the physically disabled person with his hand movement or his hand gesture recognition using MEMS technology. The use of powered wheel chair with high navigational intelligence is one of the great steps towards the integration of severely physically disabled people. Driving wheel chair in domestic environments is a difficult task for people with arm or hands impairments .The wheel chair is developed to overcome the above problem described above allowing the end users to just perform safe movements and accomplish some daily life important tasks.
Keywords: MEMS; Powered wheel chair